K-maps: Devices for capturing research ideas - Dreher, Heinz (The Information Institute, 2005)
During a field study (Dreher 1997) in which the aim was to explore and document the knowledge creation behaviour of researchers from varying disciplines, the field notes (and audio recordings) made during semi-structured interviews were augmented by drawings. These line drawings, annotated with text, became useful as a reference for continuing discussion and elaboration of the ideas which emerged during the interviews. In fact, they became so useful for subsequent communication of complex concepts that they were formally named and emerged as a fortuitous and unforeseen research outcome. This paper presents the concept of knowledge-maps (or K_maps for short) and contrasts them with similar devices such as mind maps and cognitive maps.